Cross-border M&As and eco-environmental performance of European energy utilities - Evgenii Monastyrenko (FIW - Research Centre International Economics, 2016)
European electricity industry has recently come through liberalization. Surge of intakes with high share of cross-border deals was market players' response. Measuring of post-merger performance alterations is a central question of M&A literature. EU energy sector is responsible for significant part of global greenhouse gas emissions. Its efficiency should be regarded with respect to ecological dimension. This study addresses combined economic and environmental performance of 15 biggest European energy producers in 2005-2013. I exploit Data envelopment analysis (DEA) with CO2 as an undesirable output. Panel fractional regression model with financial controls is used to isolate effects of completed mergers. Results suggest that in short term firms profit from selling their subsidiaries to foreign counter-parties. This effect doesn't sustain over time. Same-type domestic deals are detrimental in short run, but performance-enhancing in long term. Domestic and cross-border acquisitions immediately damage performance. Later ones stimulate efficiency in the long run.
Keywords: F21; G34; L25; L94; D24; 330; Mergers and acquisitions; firm performance; data envelopment analysis; fractional regression model; electric power industry; carbon dioxide emissions